Potências da imagem e sociedade de controle na Filosofia de Gilles Deleuze - Carvalho, Eduardo Francelino de (2020)
The idea of image runs through the philosophy of Gilles Deleuze in all his moments from different remarkable perspectives. In fact, a philosophy of difference could not be fixed on a single essential or even ontological definition of image, as in the case of several other concepts used by Deleuze, the concept of image presents itself differently at each moment in function of each specific problem around of which it is positioned. It is this path of the idea of image - which, although it keeps connections and continuities, is also an uncentered, non-linear, bifurcated, non-chronological path, and even, in a certain sense, endowed with its own, aberrant logic - that the present work seeks go along; from three distinct parts, each dedicated to a specific problem unfolded in more or less distinct fields of philosophy itself: in the first instance, we will deal with the image as an image of thought from a noological perspective; in a second moment of the image entering the era of modern technique, under an aesthetic perspective, with studies on cinema and painting and, finally, approached from an ethical and political perspective, the moment when the image associated with language, merges decisively to information technology and enters the era of control, no longer serving a noetic function or an aesthetic function - not aiming at a pedagogy of the spirit or an embellishment of the world - but simply at a social, technical and political function under the umbrella of integrated world capitalism, and its absolute computerization. the transition from a markedly disciplinary society to a global control society.